The Business of Coupons-Do coupons lead to repeat purchases? - Margaret P Ross (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
In recent years, couponing has emerged as a pop culture phenomenon. Businesses of all types are taking advantage of this resource by revamping their out-dated programs and turning them into something fresh to excite customers. Many questions remain unanswered concerning the viability, profitability, and usefulness of coupons. This study is an analysis of the effectiveness of coupons in enticing return purchases in the soft-drink category and the effectiveness of price discriminating at this grocery store chain. The dataset is comprised of household level grocery store transactions compiled by dunnhumby USA for 2,500 households over a period of two years. An ordinary least squares regression technique is employed to analyze the dollar sales and unit sales in the soft drink category before, during, and after coupon usage. Analysis of this sample leads to the conclusion that coupons are not effective in creating repeat purchases. However, coupons do an adequate job of price-discriminating and allow retailers to reach consumers who otherwise may not have tried a certain product.
Keywords: marketing; behavioral economics; coupons